En Sofia mathitefsantes : essays in Byzantine material culture and society in honour of Sophia Kalopissi-verti - Diamanti, Charikleia; Vassiliou, Anastasia; Arvanitē, Smaragdē I.; Kalopissi-Verti, Sophia (Archaeopress archaeology., 2019)
Essays in Byzantine Material Culture and Society in Honour of Sophia Kalopissi-Verti contains a collection of thirty studies dedicated to Sophia Kalopissi-Verti by her students which celebrate the multifaceted academic and teaching career of Professor Kalopissi-Verti, Emerita of Byzantine Archaeology at the National and Kapodistrian University of Athens. The contributions cover a large variety of topics presenting unpublished archaeological material, suggesting new approaches to various aspects of Byzantine archaeology, material culture and art history. Geographically topics span a vast area from Constantinople to South Sinai and from Cyprus and Antiocheia to the Aegean Islands, continental Greece and Italy.